Isolation, Molecular Identification and Antibacterial Activity of Endophytic Bacteria from the Bark of Plumeria acuminata - Lalu Zulkifli; Dewa Ayu Citra Rasmi; AA Sukarso; Yayuk Andayani; Dwi Soelistya Dyah Jekti (Jurnal Penelitian Pendidikan IPA, 2022)
Endophytic bacteria are able to produce bioactive compounds that are important for applications in the medical field. This study aims to isolate, identify and test the antibacterial activity of endophytic bacteria from the bark of Plumeria acuminata growing in the Mataram area. Isolation was carried out using four types of media, namely NA, TSA, MAC, and BHI. The well diffusion technique was used to test the inhibitory ability of the endophytic bacterial extract against the test pathogenic bacteria. The four test bacteria used were S. aureus, B. cereus, P. aeruginosa, K. pneumoniae. Isolates that showed inhibitory activity were then identified morphologically, biochemically and molecularly based on the 16S rRNA gene. The results of the isolation process obtained 35 colonies. where 9 of them inhibit the growth of test bacteria. There were 2 isolates that able to inhibit the growth of 4 types of test bacteria with an average clear zone diameter of very strong category (21–30 mm), namely isolates T1 and T2. The N2 isolate had the highest average inhibition zone compared to all isolates of endophytic bacteria, which was 32 mm, but was specific for P. aeruginosa. Two isolates, namely B1 and M3 gave various growth inhibitory effects with strong to very strong categories. Other isolates showed various antibacterial effects against at least 2 types of test bacteria. S. aureus was the most resistant pathogenic bacteria to the treatment of endophytic bacterial isolate extract. The cell shape of all endophytic isolates was streptobacillus with or without spores, and 50% of them were Gram-positive. Molecular identification based on the 16S rDNA gene grouped the 9 isolates into 2 main clusters, namely the genus Bacillus and the genus Pseudomonas. Isolates that were closely related to the genus Bacillus showed higher inhibitory activity than those of Pseudomonas. The results showed that isolates of endophytic bacteria from the bark of P acuminata have the potential as an important source of antibacterial substances.